String processing and information retrieval : 24th International Symposium, SPIRE 2017, Palermo, Italy, September 26-29, 2017, Proceedings /: 24th International Symposium, SPIRE 2017, Palermo, Italy, September 26-29, 2017, Proceedings. (2017) - Unknown
No abstract available